Expert System Diagnosa Gangguan Autisme Secara Dini Pada Anak dengan Metode Forward Chaining - Fuad, Evans; Aminullah, Rabiah; Soni, Soni; Rizki, Yoze (Building of Informatics, Technology and Science (BITS), 2022)
Autism is a developmental and behavioral disorder of children where social relationships are disrupted, namely children with autism cannot interact with other people, including their parents. Autistic children experience disorders such as communication disorders, social relationship disorders, and behavioral disorders, resulting in a child. Parents often do not realize the differences and abnormalities that appear in their children until they are three years old. They just realized that their child is different from other children. There are several basics of treating autism and there are some teachers who can help cure autism in children. The teacher treats autistic children with an approach that is adapted to the problem. Types of autism basically this child is divided into four categories, including social interaction disorders, behavioral generalized disorders, communication disorders, and self-stimulation disorders. This research designs and builds an expert system (expert system) for diagnosing Autism disorders in early childhood based on the web Method of Forward Chaining. This Forward Chaining is very good to use if the work starts with recording the initial information and wants to reach the completion or final goal. This expert system is considered capable of providing information and solutions for parents, about the types of autism disorders in early childhood, based on the symptoms entered and can provide solutions